ϕ28.6 mm High-Strength Anchor Cable Control Technology for Deep Soft Rock Roadways - Zang, Xianda (International Journal of Natural Resources and Environmental Studies, 2026)
Aiming at the engineering challenge of large surrounding rock deformation and conventional support failure in soft rock roadways under deep high stress and intense mining-induced conditions, this paper takes the 1101 roadway of Hudi Coal Mine as the engineering background. Adopting a combined method of theoretical analysis, numerical simulation, and field tests, this paper reveals the hierarchical coupling control mechanism of high-strength anchor cables and grouting reinforcement, optimizes and determines the support parameter system of "short anchor cables + long anchor cables + deep-shallow grouting" based on ϕ28.6 mm large-diameter high-strength anchor cables, and carries out industrial field tests. The results show that, compared with the original support scheme, the convergence of the two roadway sides, roof subsidence, and floor heave are reduced by 47.9%, 46.2%, and 40.1% respectively with the proposed technology. The surrounding rock deformation is effectively controlled, which provides a technical reference for surrounding rock stability control of similar deep soft rock roadways under strong dynamic pressure